(untitled) (Fiep Bulletin - online, 2015)
These issues are reunited in a volume with 288 pages with pictures of exercises allusive to texts devoted to numerous lessons of physical education for elementary schools. The Introduction is written by M. Emmanuel Crenier, Dr. in P. E. and Inspector of Physical Education and open Air Activities in the City of Liège.